The Antioxidant Status and Biochemical Parameters in Kid Goats Naturally Infected with Peste Des Petits Ruminants Virus - Baydar, Ersoy; Yuce, Abdurrauf; Gurcay, Metin; Kizil, Omer (Univ Fed Rio Grande Do Sul, 2018)
Background: Peste des petits ruminants (PPR) is an acute and highly contagious viral disease of small ruminants. The disease is high economical importance because of the high mortality rate. Oxidative stress is an active field of research in small ruminant medicine and has been implicated in numerous disease processes including sepsis, mastitis, acidosis, enteritis, pneumonia, respiratory, and joint diseases. Compared to human medicine, only a limited number of conditions have been investigated in regard to the effects of oxidative stress in small ruminants. The aim of this study was to determined and compared the oxidative status and some biochemical parameters in kid goats with PPR. Materials, Methods & Results: The study was performed on 15 healthy hair of kid goats (control group) and 15 kids naturally infected with Peste des Petits Ruminants (PPR). Competitive enzyme linked immunosorbent assay (C-ELISA) was used for serological detection of PPRV specific antibodies, and a reverse transcription polymerase chain reaction (RT-PCR) was performed for the detection of PPR virus. Concentrations of plasma biochemical parameters were analysed by a clinical chemistry analyser, and blood biochemical indices determined, including total protein, albumin, alkaline phosphatase (ALP), aspartate amino transferase (AST), gamma-glutamyl transferase (GGT), lactate dehydrogenase (LDH), glucose, very low density lipoprotein (VLDL), low density lipoprotein (LDL), high density lipoprotein (HDL). The plasma CAT activity, plasma GSHPx activity and plasma lipid peroxidation level was measured according to the specific methods. Besides, vitamin C values were colorimetrically determined using a phosphotungustic method acid method and vitamin E values were determined spectrophotometrically method. Plasma MDA concentrations were markedly increased in the group of kid goats with PPR (P < 0.001) whereas GSHPx (P < 0.01), and CAT (P < 0.01) activities were significantly depressed as well as concentrations of vitamins E (P < 0.05) and vitamin C (P < 0.001). Significant differences between groups were showed relative to plasma total protein (P < 0.05), albumin (P < 0.05), ALP (P < 0.05), AST (P < 0.01), GGT (P < 0.05), LDH (P < 0.05), glucose (P < 0.001), VLDL (P < 0.05), LDL (P < 0.01), and HDL (P < 0.05) Discussion: The clinical and postmortem findings of PPRV infection may be sufficient for the diagnosis in the endemic areas, yet labaratory confirmation is essential for definitive diagnosis because of the clinical similarity of PPR to rinderpest. In this study used both C-ELISA and RT-PCR in the diagnosis of suspected disease. The decrease level of VLDL, LDL, and HDL in the kids with PPR were consistent findings with liver damage, and the cause of decrease could be inadequate synthesis of cholesterol that main structure of lipoproteins due to liver dysfunction. Plasma MDA concentrations were found to be increased in the kid goats with PPR compared to the control group, while decreases of GSHPx and CAT activities were observed. Because of GSHPx and CAT are involved in the conversion of radicals into less effective metabolites, these changes coupled to the increase of MDA concentrations, suggest that an excessive ROS production occurred during PPR infection. This study has highlighted the occurrence of an oxidative stress with important differences in antioxidant status as reflected by assessment of some enzymatic and non-enzymatic antioxidants in kids infected by PPRV. In conclusion, this study has highlighted the occurrence of an oxidative stress with important differences in antioxidant status as reflected by assessment of some enzymatic and non-enzymatic antioxidants in kids infected by PPRV. Furthermore, the liver was effected by PPRV infection.
Keywords: Linked-Immunosorbent-Assay; Polymerase-Chain-Reaction; Competitive Elisa; Oxidative Stress; Differential-Diagnosis; Rinderpest Virus; Free-Radicals; Antibodies; Sheep; Baculovirus